General Synod of the Church of Ireland: May 2017. (23rd January 2018) - Turner, Kate
Abstract : This year's General Synod, the third meeting of the triennium, was held in Limerick City in a hotel with conference facilities. It was the first time that the General Synod had met in the Diocese of Limerick and Killaloe. The Synod passed Bills relating to ecumenical canons, General Synod membership and confirmation registers, as well as the ongoing area of pensions. There was also a Bill fixing anomalies relating to cross-references in the Constitution following the consolidation of part of the Constitution at last year's General Synod. Bills relating to the table of contents of the Book of Common Prayer were also passed.